INFORMATION SECURITY SYSTEM INTERNET BANKING SERVICES IN BANKING TRANSACTIONS - Samsul Arifin (Nindikayla Institute, 2023)
Information and communication technology development has a tremendous impact on almost all sectors, including the banking sector. In improving services to customers and in line with the rapid development of technology, banks meet customer needs in the form of banking products through information technology systems such as internet banking. The banking industry adopts Internet technology to develop services. This opportunity is used by banks in Indonesia, both state and private banks. Internet Banking makes it easier for customers to do banking transactions online, both financial and non-financial transactions except for making cash deposits or withdrawals. However, when using Internet Banking services is it safe? Because when using the Internet, communication devices or computer devices are connected to the global computer network, so it is very vulnerable to security attacks or Internet Banking crimes. Therefore, this paper explains the concept of security, the benefits of internet banking, how to form security attacks against Internet Banking. Later in this paper also explains how to prevent attacks or crimes in Internet Banking. This paper also explains the security models of Internet Banking and compares Internet Banking services from several banks in Indonesia both facilities and security. So that bank customers who want to use Internet Banking services gain knowledge and can choose banks that provide better and safer Internet Banking service security and can reduce online crime rates, especially in Internet Banking services